Jenny from Thebes [compact disc] (Merge Records, 2023)
The album began its life as many albums by the Mountain Goats do, with John Darnielle playing the piano until a lyric emerged. That lyric became Jenny III, a song which laid down a challenge he'd never taken up before: writing a sequel to one of his most beloved albums: All Hail West Texas. Recorded at Tulsa, Oklahoma's legendary Church Studio with Grammy-winning producer/engineer Trina Shoemaker, this is a lush collection of showtunes, pushing Darnielle as a vocalist and the Mountain Goats as a band, broadening their sonic palette once again by leaning into influences like Godspell, Jim Steinman, and the Cars.